Living with Tiny Aliens : The Image of God for the Anthropocene - Pryor, Adam (Groundworks (New York, N.Y.), 2020)
Astrobiology is changing how we understand meaningful human existence. Living with Tiny Aliens seeks to imagine how an individuals' meaningful existence persists when we are planetary creatures situated in deep time--not only on a blue planet burgeoning with life, but in a cosmos pregnant with living-possibilities. In doing so, it works to articulate an astrobiological humanities. Working with a series of specific examples drawn from the study of extraterrestrial life, doctrinal reflection on the imago Dei, and reflections on the Anthropocene, Pryor reframes how human beings meaningfully dwell in the world and belong to it. To take seriously the geological significance of human agency is to understand the Earth as not only a living planet but an artful one. Consequently, Pryor reframes the imago Dei, rendering it a planetary system that opens up new possibilities for the flourishing of all creation by fostering technobiogeochemical cycles not subject to runaway, positive feedback. Such an account ensures the imago Dei is not something any one of us possesses, but that it is a symbol for what we live into together as a species in intra-action with the wider habitable environment.